A systematic review of Toxoplasma gondii antigens to find the best vaccine candidates for immunization. (January 2019) - Rezaei, Fatemeh; Sarvi, Shahabeddin; Sharif, Mahdi; Hejazi, Seyed Hossein; Pagheh, Abdol sattar; Aghayan, Sargis A.; Daryani, Ahmad
Abstract: At present, there is not any available accepted vaccine for prevention of Toxoplasma gondii ( T. gondii ) in human and animals. We conducted literature search through English (Google Scholar, PubMed, Science Direct, Scopus, EBSCO, ISI Web of Science) scientific paper databases to find the best vaccine candidates against toxoplasmosis among T. gondii antigens. Articles with information on infective stage, pathogenicity, immunogenicity and characterization of antigens were selected. We considered that the ideal and significant vaccines should include different antigens and been expressed in all infective stages of the parasite with a high pathogenicity and immunogenicity. Evaluation within this systematic review indicates that MIC 3, 4, 13, ROP 2, RON 5, GRA 1, 6, 8, 14 are expressed in all three infective stages and have pathogenicity and immunogenicity. MIC 5, ROM 4, GRA 2, 4, 15, ROP 5, 16, 17, 38, RON 4, MIC 1, GRA 10, 12, 16, SAG 3 are expressed in only tachyzoites and bradyzoites stages of T. gondii with pathogenicity/immunogenicity. Some antigens appeared to be expressed in a single stage (tachyzoites) but have high pathogenicity and induce immune response. They include enolase2 (ENO2), SAG 1, SAG5D, HSP 70, ROM 1, ROM 5, AMA 1, ROP 18, RON2 and GRA 24 . In conclusion, current vaccination against T. gondii infection is not satisfactory, and with the increasing number of high-risk individuals, the development of an effective and safe specific vaccine is greatly valuable for toxoplasmosis prevention. This systematic review reveals prepare candidates for immunization studies.